Rancang Bangun Sistem Pakar Mendiagnosa Penyakit Tanaman Kelapa Sawit Menggunakan Metode Bayes Berbasis Android (Studi Kasus : Perkebunan PTPN 4 Air Batu) - Muhammad Dedi Irawan; Muhammad Khairi Ikhsan Nasution ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - PT. Perkebunan Nusantara IV Air Batu (PTPN IV) is a government-owned oil palm plantation that is engaged in the production of palm fruit, oil palm plants will grow well and produce optimally if the plant is protected from disease. However, there is an imbalance where every year palm oil needs increase, while oil palm production decreases. This is due to lack of understanding of plantation assistants on the types of diseases found in oil palm plants which can cause continuous damage to oil palm plants. The Bayes method is one method that is suitable for selection, because the Bayes method is a good method in machine learning based on training data using conditional probabilities as the basis. With this expert system it is expected that plantation assistants can find out the type of disease and its solution quickly so that the problem of decreasing oil palm production can be overcome. The results of the research in the form of an expert system diagnose the disease of oil palm plants using the Android-based bayes method thus, this application can be used to analyze diseases using cellular phones. Keywords - Palm Oil Disease, Expert Systems, Bayes Method, Android.